Plein Soleil : Un été des centres d'art. - Tissier, Noëlle; Avrilla, Jean-Marc; Mangion, Éric; Parisi, Chiara; Lanavère, Marianne; Assocation françcaise de développement des centres d'art; Enjalran, Muriel ([S.l.] : Association française de développement des centres d'art, 2008)
Adler, Fanny ; Bartoloméo, Joël ; Bircher, Pascal ; Blocher, Sylvie ; Brotherus, Eline ; Calle, Sophie ; Collectif 1.0.3 ; Di Corcia, Philip-Lorca ; Dietman, Erik ; Discrit, Julien ; Goldin, Nan ; Grandmaison, Pascal ; et al.
Different locations in France, 1 June to 30 September 2007.
kunstcatalogus